Digital thickness meter using infrared sensor - Wayopat, Onuma; Awikunprasert, Panatsada (Journal of Associated Medical Sciences, 2017)
Introduction: Knowing of patient thickness helps to determine the proper current and voltage of x-ray tube. Lesions on radiographs can be clearly seen and provide an accurate diagnosis. Implementation of microcontrollers and infrared sensors for digital thickness measurement can reduce time spending in thickness measurements providing a convenient way to measure the thickness without touching patient. Objectives: Purposes of the study was to design and create a digital patient thickness meter using infrared sensor. Digital display provides an accurate and precise reading value. It was easily used, real time measurement, and touchless method. Materials and methods: Digital thickness meter was calibrated and tested for the efficiency. Three different measurements of body’s thickness were compared. These values were measured from a traditional method using caliper, digital thickness meter, and digital thickness meter with a volunteer holding a smooth board. Results: The result showed that digital meter has an error of 6%. There was a linear relationship between thickness values measured from calipers, digital meter (R²=0.7993 and digital meter with holding a smooth board (R²=0.8756). Statistical analysis showed that there was a significant difference between the thickness from caliper compared to digital meter with holding a smooth board (p<0.05). Thickness measurement in male volunteers provided more accurate result than female. Use of digital thickness meter with holding a smooth board was more accurate than using digital thickness meter alone. Conclusion: Digital thickness meter using infrared sensor is a cheap, lightweight, and touchless measurement. However, the precision and accuracy of meter depend on the efficiency of infrared sensor which is a reflection property and surface absorption of material. Moreover, movement and breathing of volunteers affect the accuracy of measurement.